Scientific computing, computer arithmetic, and validated numerics : 16th International Symposium, SCAN 2014, Würzburg, Germany, September 21-26, 2014. Revised selected papers /: 16th International Symposium, SCAN 2014, Würzburg, Germany, September 21-26, 2014. Revised selected papers. (2016) - Unknown
No abstract available